Apakah Budaya Mendorong Kinerja? Peran Mediasi Inovasi terhadap Pengaruh Budaya Minangkabau terhadap Kesuksesan UMKM Milik Perempuan - Febrianti Hasnah, Eicha; Rodiah, Siti; Putri, Annie Mustika (Akuntansi & Ekonomika, 2025)
This study aims to analyze the influence of Minangkabau culture on the performance of women-owned MSMEs in Pekanbaru and the mediating role of innovation. Women play a vital role in MSMEs that significantly contribute to the national economy, while Minangkabau culture is known for its matrilineal values. A quantitative method was applied using questionnaires from 100 Minangkabau women entrepreneurs. Data were analyzed using SEM-PLS. Results show that Minangkabau culture does not significantly affect innovation or MSME performance. Conversely, innovation has a positive and significant impact on performance. Innovation also does not mediate the effect of culture on performance. These findings emphasize that innovation is the key factor in improving women-owned MSME performance in urban settings, while cultural values require structural support to contribute more effectively.